The number of fundamental constants from a spacetime-based perspective - Matsas, George E. A. [UNESP]; Pleitez, Vicente [UNESP]; Saa, Alberto; Vanzella, Daniel A. T. (Springer Nature, 2024)
We revisit Duff, Okun, and Veneziano’s divergent views on the number of fundamental constants and argue that the issue can be set to rest by having spacetime as the starting point. This procedure disentangles the resolution in what depends on the assumed spacetime (whether relativistic or not) from the theories built over it. By defining that the number of fundamental constants equals the minimal number of independent standards necessary to express all observables, as assumed by Duff, Okun, and Veneziano, it is shown that the same units fixed by the apparatuses used to construct the spacetimes are enough to express all observables of the physical laws defined over them. As a result, the number of fundamental constants equals one in relativistic spacetimes.
Keywords: Duff-Okun-Veneziano controversy; Fundamental constants; Physical units